Advanced speech communication - de la Cruz, Edna M.; Enriquez, Lina P. (Manila, Philippines : REX Bookstore, 2009)
The materials are presented in the order in which, according to the authors' collective experiences, the types of speech difficulty that occur most often and affect intelligibility.
Part I. Fundamentals of speech communication -- Part II. Speech Activities.
Includes bibliographical references and index.
Keywords: SPEECH -- COMMUNICATIION